The Role of Emotional Intelligence in Leadership and Business Success - Dewangan , Danesh Kumar (International Journal of Rehabilitation and Special Education (IJRSE), 2025)
Emotional Intelligence (EI) has emerged as a critical factor in leadership effectiveness and business success. This paper explores the role of EI in leadership by analyzing key components such as self-awareness, self-regulation, motivation, empathy, and social skills. It examines how emotionally intelligent leaders enhance workplace culture, decision-making, and team performance. Furthermore, the paper highlights the business benefits of EI, including improved employee engagement, reduced turnover, and increased organizational resilience. The study concludes that developing EI competencies is essential for sustainable leadership and long-term business success.
Keywords: Emotional intel ligence; leadership; business success; workplace culture; decision-making; self-aware ness; empathy; motivation; employee engagement; orga nizational resilience